PERLINDUNGAN HUKUM TERHADAP PEREMPUAN DAN ANAK KORBAN KEKERASAN DALAM RUMAH TANGGA (STUDI PENETAPAN NOMOR: 02/PEN.PID/KDRT/2020/PN. Mdn) - Syarifuddin, Syarifuddin; Rahmadani, Gema; Ali, Siti Husniyyah (Universitas Islam Sumatera Utara, 2023)
Legal protection for women and children is highly prioritized as a state commitment as emphasized in Article 28D Paragraph (1) of the 1945 Constitution of the Republic of Indonesia. Violence becomes a phenomenon in life, not only in the public sphere, but also in the domestic sphere which gives rise to violence in the household (KDRT). ). Husband and wife relationships should ideally be built in a harmonious and happy atmosphere, but many wives experience acts of violence from their husbands, both physically, psychologically, sexually and economically. Victims of domestic violence find it difficult to express the suffering they experience to law enforcement, because of the strong view that the husband's abusive treatment of his wife is part of a personal event, so he cannot be reported to the police, besides, he is worried that the husband will be more abusive to himself after his wife returns to his house because there is no legal protection from the police and/or courts. Even some of the wives of victims of domestic violence chose to hold back the suffering she goes through because she worries about her future if her husband has anything to do with law enforcement. 1 Dosen Fakultas Hukum UISU This study uses a normative juridical method. The approach used is legislation, concept and case analysis. primary and secondary legal materials. Collection technique through literature study and qualitative analysis. Fulfillment of the rights of victims of domestic violence based on Article 10 letter a of the PKDRT Law in Designation Number: 02/PEN.PID/KDRT/2020/PN. MDN, has not provided legal certainty, justice and benefits for victims, because there is no firm action from law enforcement officials if protection for victims based on court decisions is not implemented, because these decisions are only declarative in nature and do not have executorial power. The implementation of the protection order without the victim's perspective is evidenced by the absence of a firm court order to limit the perpetrator's space for movement, the prohibition to enter the shared living space, the prohibition to follow, supervise or intimidate the victim. victims (Explanation of Article 31 Paragraph (1) letter a of the PKDRT Law), so that court decisions in criminal cases only explain or stipulate a situation so that it does not need to be implemented, which results in not having legal force based on court products.